Blood eosinophils levels in a Colombian cohort of biomass-and tobacco-related COPD patients - García Morales, Olga Milena; Cañas-Arboleda, Alejandra; Rodríguez Malagón, María Nelcy; Galindo Pedraza, Javier Leonardo; Rodríguez Torres, Paola; Avendaño Morales, Violeta Rosa; González-Rangel, Andrés Leonardo; Celis-Preciado, Carlos A. (Frontiers in Medicine, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is a major cause of illness and death among adults. In 2019, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy incorporated blood eosinophils as a biomarker to identify patients at increased risk of exacerbations which, with the history of exacerbations during the previous year, allows identification of patients who would benefit from anti-inflammatory treatment to reduce the risk of future exacerbations. The aim of this study was to describe demographic and clinical characteristics, eosinophil counts, and exacerbations in a cohort of COPD patients stratified by clinical phenotypes (non-exacerbator, frequent exacerbator, asthma-COPD overlap) in a Colombian cohort at 2600 meters above sea level. Methods: A descriptive analysis of a historical cohort of patients with a confirmed diagnosis of moderate to severe COPD (FEV1/FVC < 0.7 and at least one risk factor for COPD) from two specialized centers with comprehensive disease management programs was performed from January 2015 to March 2019. Data were extracted from medical records one year before and after the index date. Results: 200 patients were included (GOLD B: 156, GOLD E: 44; 2023 GOLD classification); mean age was 77.9 (SD 7.9) years; 48% were women, and 52% had biomass exposure as a COPD risk factor. The mean FEV1/FVC was 53.4% (SD 9.8), with an FEV1 of 52.7% (20.7). No differences were observed between clinical phenotypes in terms of airflow limitation. The geometric mean of absolute blood eosinophils was 197.58 (SD 2.09) cells/µL (range 0 to 3020). Mean blood eosinophil count was higher in patients with smoking history and frequent exacerbators. At least one moderate and one severe exacerbation occurred in the previous year in 44% and 8% of patients, respectively; during the follow-up year 152 exacerbations were registered, 122 (80%) moderate and 30 (20%) severe. The highest rate of exacerbations in the follow-up year occurred in the subgroup of patients with the frequent exacerbator phenotype and eosinophils ≥ 300 cells/µL. Discussion: In this cohort, the frequency of biomass exposure as a risk factor is considerable. High blood eosinophil count was related to smoking, and to the frequent exacerbator phenotype.